2017
DOI: 10.18697/ajfand.78.harvestplus11
|View full text |Cite
|
Sign up to set email alerts
|

Marketing biofortified crops: insights from consumer research

Abstract: As the market for biofortified seed and food grows, farmers increasingly market their excess production to consumers. To develop a global strategy for consumer marketing of biofortified crops, research is needed to understand consumer perceptions, insights, and behaviors around food, agriculture, nutrition and biofortification. Findings from some unpublished research on these topics are reported here. In regions of Nigeria, most farmers and consumers feel positively about biofortification and are interested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Furthermore, it shows that educated participants are more likely to accept Zn-biofortified wheat than less-educated respondents. Previous studies showed similar results and supported our study findings ( 14 , 53 56 ). For instance, Tumuhimbise et al in 2013 and Siwela and his colleagues in 2020 conducted studies.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it shows that educated participants are more likely to accept Zn-biofortified wheat than less-educated respondents. Previous studies showed similar results and supported our study findings ( 14 , 53 56 ). For instance, Tumuhimbise et al in 2013 and Siwela and his colleagues in 2020 conducted studies.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies showed similar results and supported our study findings (14,(53)(54)(55)(56). For instance, Tumuhimbise et al in 2013 and Siwela and his colleagues in 2020 conducted studies.…”
Section: Results Of Multivariate Analysissupporting
confidence: 92%
“…To ensure the acceptance and effective adoption of biofortified crops among vulnerable populations, promotional activities are essential. Projects aimed at promoting biofortified crops need to utilise intensive nutrition education and extension activities [ 133 ]. The important platforms that can be used to increase the adoption and awareness of biofortified crops, while targeting nutritionally vulnerable populations, include nutrition educational programmes held at health clinics and in homes [ 134 ].…”
Section: Consumer Acceptability Of Biofortified Foodsmentioning
confidence: 99%
“…In the third working group, in "market and marketing" studies, the research question is often aimed at gathering information on the concept of biofortification, to understand the association that is made by the market and consumer, but also to analyze how biofortification is understood, the positions for and against biofortification, the associated benefits arising from biofortification and the consumption of products associated with nutrition, but also cues for names and logos to communicate the idea of biofortification chosen by consumers [46,47].…”
Section: Biofortification Economy and Marketmentioning
confidence: 99%
“…According to other studies, one way to raise consumer awareness of biofortified crops, foods and market demand for these products have been and are through the use of social marketing [47,[60][61][62]. Social marketing of biofortified crops was created to increase awareness and understanding of concepts such as hidden hunger.…”
Section: Biofortification Economy and Marketmentioning
confidence: 99%